2003
DOI: 10.1103/physrevb.68.104410
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atomic relaxations on magnetic properties of adatoms and small clusters

Abstract: Performing ab initio and tight-binding calculations we demonstrate the effect of atomic relaxations on the magnetic properties of Co adatoms and Co clusters on the Cu͑001͒ surface. Atomic relaxations decrease the spin and orbital magnetic moments and drastically affect the magnetic anisotropy of the Co adatom. We show that due to relaxations the in-plane magnetization of the Co adatom is stabilized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 39 publications
(34 reference statements)
5
29
0
Order By: Relevance
“…As mentioned before, we have placed the Co atoms of the nanoclusters on a perfect fcc Cu lattice, making no attempt to introduce lattice relaxation. Recent parameterized calculations [36], using tight-binding Hamiltonians fitted to KKR calculations, suggest that relaxations could be present in these systems. These relaxations may change inter-atomic distances, especially in the direction perpendicular to the surface plane and, in the case of the adsorbate clusters these changes may be significant.…”
Section: Resultsmentioning
confidence: 98%
“…As mentioned before, we have placed the Co atoms of the nanoclusters on a perfect fcc Cu lattice, making no attempt to introduce lattice relaxation. Recent parameterized calculations [36], using tight-binding Hamiltonians fitted to KKR calculations, suggest that relaxations could be present in these systems. These relaxations may change inter-atomic distances, especially in the direction perpendicular to the surface plane and, in the case of the adsorbate clusters these changes may be significant.…”
Section: Resultsmentioning
confidence: 98%
“…Finally, the in-gap states provide a relatively high density of states at the Fermi energy which may profoundly alter the magnetic properties of the system, for instance: the magnetic anisotropy energy [49,50], the response of the impurities to external time-dependent perturbations [51][52][53], their magnetic stability against spin fluctuations [54], and many other phenomena. These properties are currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, calculations 24 on the magnetocrystalline anisotropy energy ͑MAE͒ of transition-metal adatoms on Ag and Au surfaces ͑where the spin-orbit coupling is strong͒ have shown that Cr and Mn adatoms have a MAE of less than 5 meV. On Ni, the effect should be weaker, as on Cu, where the MAE of a single Co adatom was calculated 25 to be less than 1 meV. Much stronger MAE was found, 2 e.g., for Co adatoms on Pt ͑MAE of the order of 10 meV͒ or for 5D adatoms on Ag and Au ͑MAE of the order of 30 meV͒, caused by the fact that the Fermi level is in the middle of the spin-down 3d shell of Co and by the strong spin-orbit coupling of the 5d adatoms and the Pt, Au, and Ag substrate.…”
Section: Limitations Of Present Calculationsmentioning
confidence: 99%